MO1043: Influenza Vaccine Awareness and Acceptance Among Individuals with Glomerulonephritis and Renal Vasculitis During the Corononavirus Disease 2019 Pandemic. (3rd May 2022) - Lim, Cynthia; Hong Liew, Zhong; Zhuan Tan, Hui; Mok, Irene; Jie Leeu, Jun; Choo, Jason
Abstract: BACKGROUND AND AIMS: Patients with glomerulonephritis may have an increased risk of influenza infection and morbidity, but vaccine coverage remained low with little data on acceptance in glomerulonephritis. We aimed to assess influenza vaccine awareness among patients with glomerulonephritis and identify determinants of vaccine acceptance. METHOD: Single-center cross-sectional study of patients with glomerulonephritis who completed a survey in the clinic or over the telephone between June and August 2021. Sociodemographic data, health literacy measured by HLS-EU-47 questionnaire, influenza and the coronavirus disease (COVID-19) vaccine awareness and determinants of vaccine acceptance according to the World Health Organization framework. RESULTS: Among 86 patients who completed the survey, influenza vaccine awareness was lower than COVID-19 vaccine awareness (75.6% versus 100%). After adjusting for the survey type, use of English language at home and at healthcare settings, higher income and professional or executive occupation were significantly associated with influenza vaccine awareness, while older age and lower education level were associated with reduced awareness. The healthcare provider was the most frequent information source and > 90% trusted that healthcare providers and the government considered the patients' best interests and gave correct information. Only half thought their medical condition and medications would affect their vaccine decision while a quarter to half did not understand how the vaccine worked and thought there were better ways to protect against infection. CONCLUSION: Healthcare providers can actively identify and advocate influenza vaccines to the unaware and overcome potential barriers to reduce influenza infections and morbidity in glomerulonephritis.